Effects of Toll-like receptor signals in T-cell neoplasms. (February 2011) - Morrison, Cori; Baer, Maria R; Zandberg, Dan P; Kimball, Amy; Davila, Eduardo
T-cell neoplasms have poor prognosis and few effective therapeutic options. Therefore, identification of factors in T-cell leukemia/lymphoma that are associated with cancer progression may represent novel therapeutic targets. Recent studies have highlighted a previously unappreciated role for the expression of Toll-like receptors (TLRs) on T cells and their effects on cell survival and proliferation. TLRs can bind exogenous molecules derived from pathogens as well as endogenous self-ligands released from damaged cells. Recent reports demonstrate that TLR engagement on primary mouse or human T cells enhances proliferation and/or cell survival. The mechanisms by which TLR stimulation on T cells influences these parameters and the different T-cell subsets that are affected by TLR stimulation are currently under investigation. Furthermore, neither the biological importance of stimulating TLRs on neoplastic T cells nor the prevalence of TLR expression in T-cell malignancies have yet to be characterized. Based on published reports and compelling preliminary data, we propose that the activation of the TLR––MyD88 signaling pathway in neoplastic T cells contributes to disease progression by reducing cell death and enhancing cell division. In this article, we present both theoretical arguments and experimental data in support of this hypothesis.